Organizational and educational change : the life and role of a change agent group - Bartunek, Jean M., 1944- (Organization and management series (Routledge (Firm)), 2003)
An exploration of the identity, work and evolution of change agent groups in organizations, with emphasis on teachers and educational change. Using a joint insider/outsider approach, it tells the story of a group of teachers who were creating change in their organization setting.